2020
DOI: 10.47391/jpma.977
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality among admitted children with complications of measles in Pakistan – an observational

Abstract: Abstract Objective: To identify the vaccination status and risk factors for mortality in children admitted with complications of measles. Methods: The retrospective study was conducted at Children Hospital, Pakistan Institute of Medical Sciences, Islamabad, Pakistan, and comprised data of children admitted with complications of measles between 2013 and 2017. Information on vaccination history, complications of measles, anthropometry, hospital stay and outcome within 15 days of admission was retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[24][25][26][27][28] A study from Pakistan reported that 63% measles patients had pneumonia. 29 We found relatively higher rates of complications development among current set of children with measles. This could have been due to the fact that during COVID pandemic, people were hesitant to head to hospitals and that could have caused a delay in management of measles, allowing more patients to develop complications before heading to a healthcare facility.…”
Section: Discussionmentioning
confidence: 57%
“…[24][25][26][27][28] A study from Pakistan reported that 63% measles patients had pneumonia. 29 We found relatively higher rates of complications development among current set of children with measles. This could have been due to the fact that during COVID pandemic, people were hesitant to head to hospitals and that could have caused a delay in management of measles, allowing more patients to develop complications before heading to a healthcare facility.…”
Section: Discussionmentioning
confidence: 57%
“…Joshi and colleagues [ 18 ] showed that in Nepal in 2004, persons with measles who were stunted had an increased relative risk (RR: 5.34 [2.31–12.36]) of death compared with persons who were not stunted. Among persons hospitalized with measles in Pakistan from 2013 to 2017, Aurangzeb and colleagues [ 28 ] estimated that there was an increased odds (OR: 6.8 [3.24–14.26]) of death among those who were stunted compared to those who were not stunted.…”
Section: Resultsmentioning
confidence: 99%
“…In South Africa from 2009 to 2010, le Roux and colleagues [ 33 ] showed that there was an association between overall weight-for-age and measles case fatality. Also, among persons hospitalized with measles in Pakistan from 2013 to 2017, Aurangzeb and colleagues [ 28 ] noted that there was an increased odds (OR: 2.93 [1.44–5.93]) of death among measles cases who were underweight compared to those who were not underweight. Coetzee and colleagues [ 34 ] showed that among pediatric hospitalized measles patients in an intensive care unit in South Africa in 2014, underweight persons had an increased relative risk (RR: 2.77 [1.38–5.55]) of death compared to persons who were not underweight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost every organ in the body is destructed by measles due to damage to mucosal membranes and transitory and profound immunosuppression. This may persist for months following measles, causing complications and may prove fatal 4 . Nonimmunization, overcrowding, malnutrition, immunological deficiency, vitamin A deficiency, infection at a young age, lack of healthcare facilities, severe consequences of measles viz pneumonia and encephalitis, are among the prominent risk factors.…”
Section: Introductionmentioning
confidence: 99%